Amelioration of salt stress tolerance in rapeseed (Brassica napus) cultivars by seed inoculation with Arthrobacter globiformis. (4th March 2022) - Stassinos, Panaiotis M.; Rossi, Massimiliano; Borromeo, Ilaria; Capo, Concetta; Beninati, Simone; Forni, Cinzia
Abstract: Salt stress represents one of the most problematic abiotic stress affecting plants worldwide. In saline soils, plants try to counteract the consequences of salt stress by physiological changes, leading to the decreasing of both osmotic and oxidative stresses. Plant growth-promoting bacteria (PGPB) can ameliorate plant stress response by several mechanisms. In this work, we focused on the effects of halotolerant strain Arthrobacter globiformis on salt stress response in Brassica napus . The strain was inoculated on seeds of three rapeseed cultivars with different levels of salt tolerance; seed germination and following first phases of development were examined in plants exposed to high salinity. Compared to not inoculated plants under the same saline conditions, the inoculated showed a better stress response in the seedling phase. Moreover, a significant increase in phenolic compounds, as well as in Phenylalanine ammonia-lyase (PAL) and Superoxide dismutase (SOD) enzymatic activities were observed in inoculated plants; the concentration of the osmolyte proline was also significantly enhanced in comparison to the not inoculated ones. A. globiformis was proved to be a promising PGPB strain and it can be a tool to counteract salt stress in quite an effective manner, even at high saline conditions.